2022
DOI: 10.3390/ma15062083
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Doping on the Topological Surface States of Crystalline Bi2Se3 Topological Insulators

Abstract: We present STM/STS, ARPES and magnetotransport studies of the surface topography and electronic structure of pristine Bi2Se3 in comparison to Bi1.96Mg0.04Se3 and Bi1.98Fe0.02Se3. The topography images reveal a large number of complex, triangle-shaped defects at the surface. The local electronic structure of both the defected and non-defected regions is examined by STS. The defect-related states shift together with the Dirac point observed in the undefected area, suggesting that the local electronic structure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The cryogenic 5-axis manipulator enables rotation in large ranges of angles, and the temperature stabilization on the sample is in the range from 6.5 to 500 K. In particular, from several possible studies, magnetic topological insulators (MTIs) were intensively researched because they represent a possible route towards manipulating quantum information, coherent spin transport, and high-efficiency catalysis [14]. In the last years, URANOS research groups have tried to understand the phenomena in magnetic MTI, concentrated on studying both the magnetism of topological insulator crystals with ferromagnetic dopants in bulk [15,16], surface magnetism on a topological insulator realized by ferromagnetic monolayer [17], the magnetism of self-organizing ferromagnetic layers separated by layers of a topological insulator which can generate FM or AFM order [18,19] and axion physics [14]. Particularly important are studies on the organization of FM layers that generate intrinsic antiferromagnetic topological insulators in bulk in the compounds MnBi 2 Te 4 /(Bi 2 Te 3 ) n .…”
Section: Present Status and Scientific Highlightsmentioning
confidence: 99%
“…The cryogenic 5-axis manipulator enables rotation in large ranges of angles, and the temperature stabilization on the sample is in the range from 6.5 to 500 K. In particular, from several possible studies, magnetic topological insulators (MTIs) were intensively researched because they represent a possible route towards manipulating quantum information, coherent spin transport, and high-efficiency catalysis [14]. In the last years, URANOS research groups have tried to understand the phenomena in magnetic MTI, concentrated on studying both the magnetism of topological insulator crystals with ferromagnetic dopants in bulk [15,16], surface magnetism on a topological insulator realized by ferromagnetic monolayer [17], the magnetism of self-organizing ferromagnetic layers separated by layers of a topological insulator which can generate FM or AFM order [18,19] and axion physics [14]. Particularly important are studies on the organization of FM layers that generate intrinsic antiferromagnetic topological insulators in bulk in the compounds MnBi 2 Te 4 /(Bi 2 Te 3 ) n .…”
Section: Present Status and Scientific Highlightsmentioning
confidence: 99%
“…We note that the nesting condition and the changes between different Fermi level contours (e.g., hexagonal vs. hexastar shapes) depend strongly on the position of the Fermi level [ 40 , 75 , 76 ] and may, thus, be highly sensitive to the doping situation of the specific sample [ 77 ]. While the size of the CDW gap, as inferred from the slight asymmetry between and , does not seem to be large enough to be resolved in ARPES [ 21 , 70 , 77 ], HAS satellite diffraction peaks clearly indicate an additional long-period component of the surface charge-density corrugation.…”
Section: Resultsmentioning
confidence: 99%
“…Luo et al reported a significant improvement in THz emission from Cu-doped Bi 2 Se 3 by suppressing a high degree of intrinsic carrier concentration [26]. However, tuning of Fermi level via counter doping or electrical gating can substantially change the surface electronic structure and surface carrier mobility [28,29]. Furthermore, the mobility of the carriers greatly affects the strength of emitted THz radiation [14].…”
Section: Introductionmentioning
confidence: 99%